Brevibacterium ravenspurgense bacteremia - Fang Xingyan; Ou Xingkun; Hu Yonglin; Daimin Xiao (IDCases, 2025)
Brevibacterium ravenspurgense infections are exceptionally rare and frequently necessitate sophisticated laboratory analyses for precise identification. In this report, we detail a case of Brevibacterium ravenspurgense bacteremia in a patient suffering from adrenoleukodystrophy, a rare hereditary metabolic disorder. The diagnosis was validated using 16S rRNA gene sequencing, emphasizing the pivotal role of advanced molecular methodologies in pinpointing uncommon pathogens.Vancomycin was the preferred antibiotic for the treatment of Brevibacterium ravenspurgense infection. This case accentuates the importance of considering rare pathogens, particularly in patients with intricate medical backgrounds.